Structural conflict under the new green dilemma: Inequalities in development of renewable energy for emerging economies. (1st November 2020) - Xu, Qinyi; Dhaundiyal, Shruti; Guan, Chuanjing
Abstract: Climate Change related concerns affect multiple international and national policy forefronts. Globally, conflicts over renewables industry between the developed and emerging economies have affected the provision of green goods-thus slowing the overall welfare of global environmental governance. This article argues that the above phenomenon is a new form of green dilemma which arises from the long-lasting issue of balancing environmental protection and economic gains. It further tracks the historical evolutionary change of green dilemma, from version 1.0 to 2.0 to the current avatar of Green Dilemma 3.0. By developing the Green Dilemma Framework, the article aims to uncover the logic underlying the industrial policies and trade conflicts between the developed and emerging economies in their energy transitions. Utilizing the US vs China and US vs India conflicts in the solar PV industries as the two group of cases, the key feature of Green Dilemma 3.0 is illustrated as the conflict over status and control of the global division of labor in the new energy industry. This article offers a novel perspective on global inequality by deconstructing the unequal global production system that can act to restrict the optimization of energy use and production in tackling climate change and thus successively hindering global environmental governance in its realization of optimal results. Underneath global climate change governance, there is an unequal global production network and political system, and both these follow a core, semi-periphery, and periphery distribution of power structure. We argue that the inequality of global production system suppresses the effects of subsidy competition and erodes the economic foundation of global climate governance. Highlights: Tracks the evolutionary change of the dilemma between environment and economy. Reveals current green dilemma to be structural conflict under unequal global production networks. Deconstructs how inequality acts to restrict the optimization of energy use and effects in tackling climate change.